Pitfalls of Paramilitarism:: The Croix de Feu, the Parti Social Français, and the French State, 1934-39 - Kennedy, Sean (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2007)
Abstract As early as 1933, the French rightist movement, the Croix de Feu, was proclaiming its willingness to threaten the use of force in order to achieve its political goals. However, this strategy proved risky for the French right, which was fragmented. Moreover, compared to its Italian and German counterparts, the French Third Republic dealt with the far right in a more robust manner; the police were reliable and the left-wing Popular Front government banned the Croix de Feu. But the group’s leader, Lieutenant-Colonel François de La Rocque, responded by creating a new right-wing group: the Parti Social Français (PSF). The PSF not only resumed many of the Croix de Feu‟s paramilitary activities, but also blamed rising political violence on the French left, an argument recently used by its predecessor. While continuing to act belligerently, the PSF claimed that the Popular Front sought to repress it and democratic liberties in general, a strategy which helped to demoralize the left and undermine the Popular Front. The Croix de Feu and the PSF did much to exacerbate the crisis of democracy that afflicted France in the late 1930s. Their tactics illustrate how the politics of the street, coupled with exploitation of the rhetoric of democracy, can weaken even long-established parliamentary systems.